Os símbolos eclesiais nacionais como ferramenta de expressão e evangelização para o designer de moda - Camara, Alexsandro Cassio (2012)
The ecclesial clothing have attracted growing interest and curiosity. The vestments, full of symbols, are an icon of the Roman Church and there is a need for specialists in the development of these products to meet this market niche that lacks options. The inclusion of national symbols emerges as a strategy to communicate the sense of belonging and bring the body of the message of the church priest.